Marine environmental pollution and offshore aquaculture structure: Evidence from China - Yuan, Bin; Cui, Yuhu; An, Dong; Jia, Zhaoxin; Ding, Wenyan; Yang, Lin (Frontiers in Marine Science, 2023)
The marine environment pollution is becoming an important factor that restricts the sustainable development of mariculture in China. This study takes 10 Chinese coastal provinces (cities) as the study area, based on the rationalization and upgrading dimensions of industrial structure, and innovatively constructs an analytical framework of marine environmental pollution and offshore aquaculture structure to identify the intrinsic relationship between them; and introduces a spatial econometric model to alleviate the estimation bias caused by the public goods attribute of marine environment and improve the reliability of research conclusions. The results show that: (1) The rationalization of the offshore aquaculture structure in China is relatively weak, showing a “concentrated and contiguous” distribution pattern towards the developed aquaculture areas; at the same time, but the differences between regions are expanding; (2) The rationalization and upgrading of the offshore aquaculture structure are affected by the pollution of the marine environment. The degree of upgrading shows different trends; (3) There is a significant spatial adjacency and threshold effect of the negative impact of marine environmental pollution on offshore farming structure. However, due to the limitations of data, the accuracy of our data and the effectiveness of the measurement of industrial structure indicators still need to be improved. Therefore, governmental departments should consider the development of the surrounding areas as well as the pollution emission in the region, and jointly promote the optimization and adjustment of China’s offshore aquaculture structure through the construction of a coordinated management mechanism of marine pollution prevention and treatment.